As imagens da mulher afro-brasileira em Olhos D'Água, de Conceição Evaristo - Araújo, Roselene Cardoso (2020)
This research develops an analysis of the book Olhos D'Água by Conceição Evaristo. The reading of the author's short stories is carried out considering the representations of images related to Afro-Brazilian women. The reading of the author's content is carried out considering the representations of images related to Afro-Brazilian women. The research starts from the perspective that Evaristo undertakes the decolonization of black women by placing her in a discursive space towards the liberation of the colonialist heritage. A posture in which the rescue of the social being prevails is a present trace in the writer's production. It is also noticed that reality and fiction are intertwined or put together, originating what the author called "escrevivência". In this process, the author highlights figures of the society in the center of the narratives who are found in the ghetto (the ignored space) and are linked to a social hierarchical chain which brings the white man at the top and, subsequently, the white woman. After them comes the black man and, finally, the black woman who, by differentiating herself from both the white woman and the white man, becomes "the other of the other", a doubly subalternized subcategory. This category of women is present in the discussions mainly relating to the pursuit of rights and visibility. This process is achieved by characters such as Ana Davenga, DuzuQuerença, Luamanda, Cida, Natalina and Salinda among others who assume autonomy over their bodies. They do that in order to overcome the objectification of the white colonial system which is responsible for controlling, animalizing and sexualizing the body of black women. It is also noticed that the emancipating consciousness undertakes the questioning of the historical conditions that generated the exclusion and submission. In the study, the conquest of the voice and the recognition of this standpoint are highlighted since the subordinate figure finds self-realization, what does not occur in a colonialist society. Also, the reading of the ancestry is developed as being a palimpsest of the culture that is sought at the heart of Afro-descendant identity. In other words, Conceição Evaristo's literary itinerary retraces the path of her female ancestry in order to (re)construct the identity of aphrodiasporic individuals. The theoretical support that directs the analyzes lies mainly in the works of authors who debate the concepts of standpoint, black feminism, female-authored literature, the intersection of gender, ethnicity and social class, as Djamila Ribeiro (2019), Luiza Lobo ( 1993), Grada Kilomba (2019), Gaytri C. Spivak (2010), bellhooks (2019), among others